Evaluación del estado nutricional de mujeres gestantes que participaron en un programa de alimentación y nutrición (2010)
ABSTRACT: Objective: To evaluate the nutritional status of a group of pregnant women and their newborn infants participating in the MANA program. Methods: Descriptive, longitudinal and prospective study designed to follow the cohort before and after intervention. Results: 53 % of the household showed food insecurity. With the program food ingestion had a significant increase and the prevalence of the risk of micronutrient deficiency diminished. The low gestational weight diminished from 27.8 % in the first trimester to 20.3 % in the third trimester. 94 % of the newborns weighed over 2500 g. Anemia was prevented in 86% of the mothers with iron deficiency. The mothers at risk of serum folate deficiency diminished from 30,8 % in the first trimester to 11,5 % in the second. Conclusion: Since the socioeconomic conditions of the population were unchanged during the study, it is possible to conclude that the MANA program and the products received had a positive and significant impact in the nutritional status of the mothers. Key words: Pregnancy; food complementation; micronutrients supplementation; nutritional education; nutritional status.